Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008042.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Triptans for acute cluster headache

Abstract: Background Cluster headache is an uncommon, but severely painful and disabling condition, with rapid onset. Validated treatment options are limited, and first-line therapy includes inhaled oxygen. Alternative therapies such as intranasal lignocaine and ergotamine are not as commonly used and are less well studied. Triptans are successfully used to treat migraine attacks and, because of this, they may also be useful for cluster headache. Objectives To determine the efficacy and tolerability of triptans for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
(85 reference statements)
1
21
0
2
Order By: Relevance
“…This SR‐MA also found that the 5‐HT blood levels were increased in the ictal compared with the interictal headache phase in episodic migraine 16‐18,58 . Even though triptans are used to treat acute attacks of migraine 59 and CH, 60 we did not observe a significant change of 5‐HT in whole blood during the ictal headache phase in CH, 55 a finding confirmed more recently 61…”
Section: Discussionsupporting
confidence: 83%
“…This SR‐MA also found that the 5‐HT blood levels were increased in the ictal compared with the interictal headache phase in episodic migraine 16‐18,58 . Even though triptans are used to treat acute attacks of migraine 59 and CH, 60 we did not observe a significant change of 5‐HT in whole blood during the ictal headache phase in CH, 55 a finding confirmed more recently 61…”
Section: Discussionsupporting
confidence: 83%
“…These additional outcomes are similar to the reporting of outcomes seen in Cochrane Reviews of acute treatments for migraine [40]; cluster headache, although not in any way comparable with TTH, also uses early outcomes because these headaches usually resolve naturally in about an hour [41]. One-hour outcomes might be particularly important in studies of formulation or route of administration of drugs in which speed of onset was an issue.…”
Section: Outcomes In Clinical Trialsmentioning
confidence: 61%
“…Le zolmitriptan oral à 2,5 mg est disponible en France, a une AMM dans le traitement de la crise de migraine, mais pas dans celui de la crise d'AVF. Enfin, une récente analyse Cochrane recommande uniquement le sumatriptan SC et le zolmitriptan pernasal, ne laissant aucune place aux triptans par voie orale [71].…”
Section: Triptansunclassified